Comparing Imputation Methods for Multivariate Time Series: A Case Study for Industrial Group Index of Thailand Stock Market - Yingpratanpron, Pongpon (KKU Science Journal, 2025)
This study investigates and compares imputation methods for multivariate time series data to identify the most effective approach. Using secondary data of stock price indices from eight industrial sectors in the Stock Exchange of Thailand, retrieved from the SETSMART database, the study covers 4,877 days from January 1, 2004, to January 1, 2024. Missing data patterns were categorized into three types: random missing, sequential missing, and block missing, with proportions set at 5%, 10%, 20%, 30%, 40%, and 50%. The imputation methods were grouped into three categories: statistical methods (mean, median, LOCF, NOCB, and linear interpolation), machine learning methods (EM, MICE, KNN, and random forest), and deep learning methods (GP-VAE, USGAN, and SAITS). Performance was assessed using root mean squared error (RMSE), mean absolute error (MAE), and mean absolute percentage error (MAPE). Results indicated that linear interpolation was the most efficient method for missing proportions below 50% across all patterns, while random forest was the most efficient method for a 50% missing data proportion.